Time flies when you’re teamworking: the teamwork flow scale. - Laneiro, Tito (2017)
The purpose of this study is to contribute to the clarification of the structural dimension of the experience of flow, and to assess teamwork flow. We developed a 36-item Teamwork Flow Scale (TFS). Using principal components (PCA) and confirmatory factor analyses (CFA), we validated the TFS in a sample of 635 Portuguese employees (Mage = 35.51, SD = 11.13) 58.1% of which were male (n = 369) from various occupational sectors. Four alternative models of flow were tested. PCA yielded a 3-factor solution (peak performance, peak experience, and time transformation). The 9 intercorrelated factors model of flow best adjusted to our sample. The TFS should be tested in other samples and cultures. This is a promising tool that can help managers become aware of how to transform work into a more rewarding and productive activity, and source of well-being, contributing to a deeper understanding of the multidimensional concept of flow.